Analisis Kesalahan Berbahasa Tataran Morfologi dan Sintaksis dalam Buku Teks Bahasa Indonesia Kurikulum 2013 Kelas XI Terbitan Kemendikbud 2016 - Rezi Miranti Desmawani; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The analysis of language errors which is the focus of this research is seen in the 2013 Curriculum Indonesian Book Class XI Published by the Ministry of Education and Culture 2016, the author still finds errors in it both at the morphological level and at the syntactic level. The problems in this study are (1) how are the language errors at the morphological level contained in the 2013 Curriculum Indonesian Language Textbook Class XI Issued by the Ministry of Education and Culture 2016?, (2) What are the syntactic language errors found in the 2013 Curriculum Indonesian Language Textbook Class XI published by the Ministry of Education and Culture? 2016?. The theory used was proposed by Setyawati (2010). The method used is content analysis, which is in the form of a description of the data and analyzed. The approach used in this research is qualitative, namely the author presents the data by taking into account the aspects of quality and quality under study. Based on the analytical research carried out, it can be concluded that (1) morphological language errors contained in the Indonesian Curriculum 2013 Curriculum 2013 Class XI textbook published by the Ministry of Education and Culture 2016 contained 21 errors, examples of omitting affixes, sounds that should melt are not melted, sound decay that should not be melted. melted, abbreviated morphs mem-, men-, meng-, meny-, and meng- (2) The language errors at the syntactic level contained in the 2013 Curriculum Indonesian Language textbooks Class XI published by the Ministry of Education and Culture 2016 contained 4 errors, examples of the use of prepositions imprecise, double plural. Influence